2002
DOI: 10.1177/0146167202281004
|View full text |Cite
|
Sign up to set email alerts
|

It’s Different when I Do it: Feature Matching in Self-Other Comparisons

Abstract: Two studies explored the application of feature-matching and cancellation models to self-other comparisons. College participants completed a questionnaire about their religious behaviors and saw another questionnaire supposedly completed by another student. Participants in Study 1 (N = 114) who were explicitly provided direction of comparison instructions showed a direction of comparison effect, rating the person whose questionnaire they saw last as more religious. Participants in Study 2 (N = 103), who were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…As expected, the tendency to show contrastive evaluative reactions was undermined when participants were attuned to shared characteristics, despite the fact that the manipulation of perceived similarity was only partially successful. This finding is consistent with other research showing that shared and unique features are adjusted to each other in comparative evaluations (Hodges et al, 2002;Houston & Sherman, 1995) and also with research showing that assimilation and contrast can be simultaneous effects (e.g. Manis et al, 1991;Mussweiler & Strack, 2000b).…”
Section: Satisfactionsupporting
confidence: 92%
“…As expected, the tendency to show contrastive evaluative reactions was undermined when participants were attuned to shared characteristics, despite the fact that the manipulation of perceived similarity was only partially successful. This finding is consistent with other research showing that shared and unique features are adjusted to each other in comparative evaluations (Hodges et al, 2002;Houston & Sherman, 1995) and also with research showing that assimilation and contrast can be simultaneous effects (e.g. Manis et al, 1991;Mussweiler & Strack, 2000b).…”
Section: Satisfactionsupporting
confidence: 92%
“…One consequence of self-construal may thus be to influence the choice of focal hypothesis in a self-other similarity judgment. Hodges et al (2002) focus on religious identity, for example, may have primed an interdependent self-construal in American participants, causing a reversed asymmetry. Religious identity emphasizes connectedness to others, and interdependence is a hallmark of religious communities, as Markus and Kitayama noted (1991, p. 228).…”
Section: Desire To Be Similar To Othersmentioning
confidence: 99%
“…One study (Hodges, Bruininks, & Ivy, 2002; Study 1) found an unpredicted significant reversal of the self-other similarity asymmetry for American students. Hodges et al first had participants judge how religious they and a comparison other were.…”
Section: Introductionmentioning
confidence: 99%
“…Because social comparison involves a comparison between a familiar entity, the self, and less familiar entity, a similar other, it is not surprising, that researchers have examined feature-matching effects in social comparison (e.g., Hodges et al, 2002;Mussweiler, 2001;Srull & Gaelick, 1983). Indeed, Srull and Gaelick's (1983) reasoning for explaining order effects in social comparison in perceived similarity by applying feature-matching theory, inspired our theoretical reasoning for explaining order effects in social prediction.…”
Section: Research On Social Comparisonmentioning
confidence: 94%
“…For example, it is possible that the use of the self in social prediction is an implicit process, but making the self explicit interrupts that implicit process from occurring. Additionally, one could investigate whether the similarity of self and other increases as a function of their common features and decreases as a function of their distinctive features (e.g., Hodges et al, 2002) or whether and how self-other correspondence in social prediction varies as a function of desirable and undesirable traits in self and others (Stapel & Koomen, 2001). …”
Section: Research On Social Comparisonmentioning
confidence: 99%